ALUM, ARBOR, WHITING ON TIE-DYED BATIK (JUMPUTAN) WITH TURMERIC DYE (CURCUMA DOMESTICA VAL) - Oksy Rimayana; Adriani Adriani (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
Tie-dye batik (jumputan) is one of the batik but made with simpler techniques and equipment. This research utilizes turmeric as a natural dye. This study aims to describe (1) the name of the color (hue), (2) fastness, (3) the difference in mordant on the name of the color (hue), fastness on batik ikat dip (jumputan) using natural coloring turmeric (curcuma domestica val). This type of research is experimental research, the data in this study are primary data sourced from 18 panelists. The data collection technique used is a questionnaire, then the data is processed and analyzed with the Friedman K-Realted Sample test. The results of the study on the name of the color (hue) without using mordant on color 1) Yellow #FFFF00, on color 2) Gold #FCF853, in color 3) Yellow #F7EF00. Alum mordant for color 1) Yellow #F4E841, color 2) Paris Daisy Yellow #F6093D, color 3) Gold #F6D620. Conifer mordant color 1) Golden Rod #D5A606, color 2) Dark Golden Rod #C59809, color 3) Dark Golden Rod #C59809. Whiting mordant color 1) Light Brown #E9CA66, color 2) Paris Daisy Yellow #EFCD51, color 3) Orange #E5B107. The results of data analysis of fastness obtained a significance of 0 which is smaller than the significance level.The effect of dyeing on washing resistance obtained a significance value of 0.001 which is smaller than the significance level of 0.000 <0.05 with the result that Ha is accepted and Hₒ is rejected. This means that there is a significant change.